Assessment of environmental safety of the atmosphere of Atyrau region (Journal of Geography and Environmental Management, 2016)
The article provides a general assessment of the environmental safety of the atmosphere of Atyrau region. The main sources of pollutants in the region, as well as the dominant substances that have a negative impact on the atmosphere were adduced. The article shows one way of evaluating the safety of the region. A category of hazards of major of oil refineries was defined, which gives the approximate assessment of the impact of the individual enterprise on environment.
Keywords: atmosphere; pollution